Decision-making on Mega-projects: Drifting on Political Discontinuity and Market Dynamics - Priemus, Hugo (European Journal of Transport and Infrastructure Research, 2010)
Decision-making on mega-projects is beset by a multitude of problems. Cost overruns and disappointing achievements are already well documented. Some of these pitfalls appear in the initial stages of the decision-making: the absence of an appropriate problem analysis, the lack of alternatives, ambiguities about scope, no programme of functional requirements, flawed process architecture and the dissemination of contested information. But all sorts of uncertainties arise in the long periods between the initiative and the start of operations. Very often, unforeseen developments are triggered by political discontinuity and market dynamics. This paper helps to address this situation by providing an overview of the impact of market dynamics and political discontinuity (which are sometimes interrelated) on decision-making on mega-projects. We analyse these impacts and attempt to determine ways in which project managers could deal with them. The identification and allocation of risks among public and private players is a crucial variable. The paper aims to contribute to theories of decision-making on mega-projects and puts forward practical recommendations for the relevant parties.